Assessment of the influence of Institutions and Globalization on environmental pollution for Open and Closed economies - Bright Akwasi Gyamfi; Divine Quase Agozie; Ernest Baba Ali; Festus Victor Bekun; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
As the environmental sustainability effectiveness of various political systems is taken into consideration, it is doubtful as to whether the presumption of the overall efficiency of democracy can be sustained in global governance architecture. The effectiveness of autocracies and democracies (i.e., governance indicators are compared in the present study) with reference to strengths and weaknesses in environmental objectives. This analysis explores the effect of autocracy, democracy, as well as the trend of globalization on CO2 emissions for open and closed economies from 1990 to 2020. Crucial indicators such as economic growth, renewable energy and non-renewable energy are controlled for while examining the roles of economic expansion on the disaggregated energy consumption portfolios for both open and closed economies. The empirical analysis revealed some insightful results. First, for the open economies, with the expectation of non-renewable energy which show a positive significant impact on emissions, all variables show a negative effect on emissions. Furthermore, the closed economies result indicate that, apart from renewable energy which has a negative relationship with emissions, all the variables including the interaction terms have a positive relation with emissions. However, an inverted U-shaped environmental Kuznets curve (EKC) hypothesis was validated for both economies.
Keywords: 330; Open economies; closed economies; democracy; autocracy; Environmental Kuznets Curve; globalization index; environmental sustainability